Pelatihan dan Pendampingan Penyusunan Lembar Kerja Peserta Didik (LKPD) bagi Guru SMPN 3 Rambah Hilir - Annajmi, Annajmi; Riska Novia Sari; Arcat; Nurrahmawati; Ratri Isharyadi; Marfi Ario; Lusi Eka Afri; Hera Deswita (Akademi Farmasi YPPM Mandiri, 2022)
LKPD as a learning resource plays an important role for students in learning activities to be actively involved in understanding concepts. The problem is that teachers have not been motivated to make their own LKPD according to the characteristics and abilities of students. This is because teachers do not understand the importance of using LKPD which are prepared by themselves in learning and the mechanics and technicalities of compiling LKPD correctly and well. The teacher only uses textbooks and LKPD which contains a summary of the material, sample questions and practice questions without any process of finding concepts. Students receive information from LKPD without being able to explore their ability to obtain information/concept discovery independently. In connection with these problems, training and assistance in the preparation of LKPD was carried out at SMPN 3 Rambah Hilir. The teacher participated in this activity enthusiastically. This can be seen from the positive response given by dmana there were 15.4% gave a very good response and 76.9% gave a good response. The material and assistance provided in the training helped teachers make a better LKPD, namely 15.4% stated that it was very good, 69.2% stated that it was good and 15.4% stated that it was quite good. Teachers became motivated to make their own LKPD, namely there were 15.4% very good, 76.9% good and 7.7% enough.